THE INFLUENCE OF INFORMATION QUALITY, INFLUENCER CREDIBILITY, AND CONSUMER TRUST ON PURCHASE DECISIONS OF AZARINE SERUM AMONG GENERATION Z - Krisminun Sangeeta; Tine Yuliantini (International Humanities and Applied Science Journal, 2026)
The aim of this research is to explore how the quality of information, the credibility of influencers, and the level of consumer trust affect the buying choices of Azarine skincare serum products among Gen Z individuals in Jakarta. The skincare industry has been rapidly expanding, and the rise of influencer marketing has notably altered consumer buying habits. This research utilized a quantitative approach, specifically through surveys. Questionnaires were given to 240 Gen Z participants who regularly use Azarine serum products to gather data. The sampling technique applied was purposive sampling. Data analysis was conducted using structural equation modeling (SEM) with the partial least squares (PLS) method, assisted by SmartPLS 4. 1 software. The findings reveal that information quality, influencer credibility, and consumer trust all significantly and positively affect purchasing decisions. Among these three factors, the quality of information stood out as the most impactful on buying choices. These results suggest that skincare companies should prioritize providing precise and trustworthy information, choosing credible influencers, and fostering consumer trust to boost purchasing behavior.